Constructed pine log piles facilitate plant establishment in mining drylands. (1st October 2020) - Oreja, B.; Goberna, M.; Verdú, M.; Navarro-Cano, J.A.
Abstract: Ecological facilitation, though accepted as a main mechanism of plant community assembly, is just starting to be utilized in restoration programmes. Constructing nurse objects that mimic the effect of natural nurse species can be an option to trigger plant nucleation processes in disturbed stressful ecosystems. We hypothesized that arranged log piles might imitate plant facilitation by alleviating abiotic stress and expanding the regeneration niche of beneficiary species, eventually promoting plant establishment, fitness and diversity. With this aim, within a pilot restoration programme in abandoned mining structures in SE Spain where climatic and edaphic stresses concur, we constructed 133 pine log piles from natural wastes generated by local silvicultural activities. We monitored 51 of them plus their adjacent open areas for 15 months, measuring soil temperature, radiation and humidity. We recorded natural seedling establishment, plant nutritional status and heavy metal accumulation. We further performed a seed sowing experiment to investigate how log piles affect plant taxonomic and functional diversity based on 11 establishment and phytostabilization traits. Pine log piles significantly softened microclimatic conditions and accelerated plant establishment in unfertile and metal-polluted mining substrates, simultaneously capturing water, providing shade and pine seeds. Plant communities that naturally established beneath the piles were 15 times denser and five times taxonomically more diverse than those in open areas, despite being skewed towards pine recruitment. Experimental communities sown under log piles were also 1.4 times functionally more diverse, as theory predicts for relaxed abiotic conditions. Log piles improved seedling nutritional status, in terms of P and K content, at the cost of increased metal accumulation. At the landscape scale, nurse objects triggered plant establishment promoting taxonomic and functional diversity in extremely stressful environments. This study exemplifies how soft restoration tools can be based on mechanisms that are widely accepted in the ecological theory. Highlights: Ecological facilitation has rarely been utilized in mine restoration programmes. Logged wood can be arranged to create nucleation points in abandoned mines. These nurse objects alleviate the abiotic stress, thus promoting plant establishment. Plants established by nurse objects are nutritionally more balanced.